En rammefast filmskolekultur - Philipsen, Heidi (K&K - Kultur og Klasse, 2007)
Om dogmer på Den Danske Filmskole A firmly framed Film School Culture: About The dogma of The National Film School of Denmark This article is dealing with the fact that culture is not only something we can study through a tradition of cultural studies. In a much younger and less explored field we find a growing interest in studying the way culture is established in different organizations. I introduce theories from this field and employ The National Film School of Denmark as an illustration of an organization that has developed a certain kind of culture based on a mix between trust and restrictions. In explaining the use of restrictions further, I introduce and elaborate on the educational term ‘scaffolding’. Through the use of several levels of scaffolding – in the learning methods and in the way the Film School is organized – this organization has created an interesting culture that produces innovation in new Danish film. My point is elaborated with help from Barry Schwartz, an American psychologist and author of the book The Paradox of Choice (2004). His research and my article are helpful for understanding how the use of scaffolding can reduce stress and complexity and thereby produce good results within the culture of an organization like The National Film School of Denmark.